Pengaruh Electronic Word Of Mouth, Online Customer Review, dan Brand Trust Terhadap Purchase Intention (Studi Kasus Pembelian Scarlett Di Kecamatan Purwodadi Grobogan) - Arnia Wijias Wati; Indah rahayu (LPPM Universitas An Nuur, 2024)
Background : Lifestyle changes are driven by technology and influenced by generation Z (millennials) who have the habit of using cosmetic products to care for or beautify the skin and support the appearance of both women and men, improving their appearance and selfconfidence. The first thing that needs to be considered when shopping online is looking for an official site that can be trusted, so that business people can build trust. This can be a choice according to their desire to behave. The importance of electronic word of mouth, online customer reviews and brand trust can influence purchasing intentions.Purpose: To purpuse the influence of electronic words of mouth, online customer reviews, and brand trust on purchase intentions (Case Study of Purchasing Scarlett in Purwodadi Grobogan District)Methods: This research uses a quantitative approach which aims to test the hypothesis formulated. Determining the number of samples used the Slovin formula with a purposive sampling technique. The sample was 94 respondents. statistical analysis techniques Statistical Program for Social Science (SPSS) version 25.Conclusion: Electronic word of mouth has no influence on purchase intention, while online customer reviews and brand trust play a role in purchase intention.Suggestion: Researchers can expand the sample to obtain more accurate and varied data. Researchers are expected to be able to develop research not only in Purwodadi District but more widely to Grobogan Regency or within the scope of Central Java.